2011
DOI: 10.1002/pon.1992
|View full text |Cite
|
Sign up to set email alerts
|

The impact of molar pregnancy on the male partner

Abstract: There are high persisting levels of anxiety in male partners of women with molar pregnancy. Partners may benefit from therapy where anxiety disorders are detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(25 reference statements)
0
9
1
Order By: Relevance
“…Despite a consistent pattern being found in the literature that most couples facing serious illnesses such as GTD find positive psychological changes in their relationships [ 9 ], this study shows how GTD could negatively impact the couple, especially when it comes to younger patients. Therefore we suggest including the partner as medical information and recommendations unfold after diagnosis [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite a consistent pattern being found in the literature that most couples facing serious illnesses such as GTD find positive psychological changes in their relationships [ 9 ], this study shows how GTD could negatively impact the couple, especially when it comes to younger patients. Therefore we suggest including the partner as medical information and recommendations unfold after diagnosis [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of researchers have found that pain can play a large role in disturbed sleep (Beck et al, 2005;Byar et al, 2006;Davidson et al, 2002;Furlani & Ceolim, 2006;Graci, 2005). As suggested in the literature, a number of reasons other than pain may cause sleep disturbance, including emotional stress, medications, depression, and other unpleasant symptoms (Bardwell et al, 2008;Beck et al, 2005;Gooneratne et al, 2007;Graci, 2005;McMillan et al, 2008).…”
Section: Pittsburgh Sleep Quality Index and MD Anderson Symptom Invenmentioning
confidence: 99%
“…The findings are of interest because most of the patients were very ill and receiving medication such as morphine, midazolame, and chlorpromazine, all of which affect the ability to remember and also could be associated with terminal illness. Bardwell et al (2008) noted that a link may exist between insomnia and mood. In their study, Bardwell et al (2008) found that depressive symptoms emerged as a significant risk factor for insomnia, something Graci (2005) between depressive symptoms, sleep disorders, and pain, and advocated good pain control as one option to improve sleep for patients.…”
Section: Pittsburgh Sleep Quality Index and MD Anderson Symptom Invenmentioning
confidence: 99%
See 2 more Smart Citations